Condition Assessment of the Conical Surface of Atomizer Needles and Seats of Marine Diesel Engines by Acoustic Emission – Preliminary Research - RAUNMIAGI, Zygmunt (Archives of Acoustics, 2011)
The condition of the conical surface of the needle and seat in a fuel atomizer can be assessed by using the acoustic emission method. The assessment of this conical tribological pair can be performed by up-to-date measurement methods that substantially enhance the quality of evaluating the technical condition of conical surfaces of the atomizer needle and seat.